Assessment of landscape sustainability of Stavropol Region to anthropogenic load - Pavel Anatolievich Didenko; Daria Sergeevna Vodopyanova; Evgeniya Andreevna Skripchinskaya (Наука. Инновации. Технологии)
In article are considered questions of the modern state, the degree of anthropogenic load and resistance to her landscapes of the Stavropol Region using a scoring method. For example, the landscapes of Stavropol Region the evaluation of anthropogenic load, defined area of lands with the targeted - environmental and resursosnabzhayuschimi functions, calculated the degree of resistance of landscapes to anthropogenic influence, which will allow to solve the problem of the efficiency of agriculture in the study area. The obtained results will allow to adjust the approaches to planning land-use systems.